Beyond “Witnessing”: Children’s Experiences of Coercive Control in Domestic Violence and Abuse - Callaghan, Jane E. M.; Alexander, Joanne H.; Sixsmith, Judith; Fellin, Lisa Chiara (Journal of interpersonal violence, 2018)
Children’s experiences and voices are underrepresented in academic literature and professional practice around domestic violence and abuse. The project “Understanding Agency and Resistance Strategies” (UNARS) addresses this absence, through direct engagement with children. We present an analysis from interviews with 21 children in the United Kingdom (12 girls and 9 boys, aged 8-18 years), about their experiences of domestic violence and abuse, and their responses to this violence. These interviews were analyzed using interpretive interactionism. Three themes from this analysis are presented: (a) “Children’s experiences of abusive control,” which explores children’s awareness of controlling behavior by the adult perpetrator, their experience of that control, and its impact on them; (b) “Constraint,” which explores how children experience the constraint associated with coercive control in situations of domestic violence; and (c) “Children as agents,” which explores children’s strategies for managing controlling behavior in their home and in family relationships. The article argues that, in situations where violence and abuse occur between adult intimate partners, children are significantly affected, and can be reasonably described as victims of abusive control. Recognizing children as direct victims of domestic violence and abuse would produce significant changes in the way professionals respond to them, by (a) recognizing children’s experience of the impact of domestic violence and abuse; (b) recognizing children’s agency, undermining the perception of them as passive “witnesses” or “collateral damage” in adult abusive encounters; and (c) strengthening professional responses to them as direct victims, not as passive witnesses to violence.